The EU as a force for peace in international cyber diplomacy - Annegret Bendiek (Stiftung Wissenschaft und Politik (SWP), 2018)
Ever since the cyber attacks against the computer networks of European governments and defence and foreign ministries have become public knowledge, security policy-makers have insisted that the EU Member States need to develop more adequate cyber-defence and cyber-retaliation capabilities. However, the EU continues to base its cyber-security strategy on the resilience of Information and Communication Technology Infrastructures and cyber diplomacy as part of its Common Foreign and Security Policy (CFSP) so as to position itself as a force for peace. Its Joint EU Diplomatic Response to Malicious Cyber Activities, adopted in October 2017, primarily stipulates non-military instruments that could contribute to 'the mitigation of cybersecurity threats, conflict prevention and greater stability in international relations'. Faced with increasing activities infrastructures, Europe would be well-advised to adhere to the step-by-step cyber-diplomacy plan, which is based on the principle of due diligence.
Keywords: 320